Fluid dynamic analysis of a continuous stirred tank reactor for technical optimization of wastewater digestion. (15th March 2015) - Hurtado, F.J.; Kaiser, A.S.; Zamora, B.
Abstract: Continuous stirred tank reactors (CSTR) are widely used in wastewater treatment plants to reduce the organic matter and microorganism present in sludge by anaerobic digestion. The present study carries out a numerical analysis of the fluid dynamic behaviour of a CSTR in order to optimize the process energetically. The characterization of the sludge flow inside the digester tank, the residence time distribution and the active volume of the reactor under different criteria are determined. The effects of design and power of the mixing system on the active volume of the CSTR are analyzed. The numerical model is solved under non-steady conditions by examining the evolution of the flow during the stop and restart of the mixing system. An intermittent regime of the mixing system, which kept the active volume between 94% and 99%, is achieved. The results obtained can lead to the eventual energy optimization of the mixing system of the CSTR. Highlights: A numerical model of a continuous stirred tank reactor is presented. The sludge flow behaviour is studied under steady and non-steady conditions. The active volume as a function of the mixing flow rate exhibits a logistic tendency. An intermittent operating regime with a high mixing quality is determined.